Research on Protection Performance of Surge Protective Devices against Electromagnetic Pulse. (11th April 2022) - Zhao, Zhongyi; Wang, Shenyu; Cui, Yongzhi
Abstract : To evaluate the protection performance of SPD (surge protective device) against electromagnetic pulse, the response ability of several typical surge protective devices to wide and narrow electromagnetic pulses was tested by using a SPD response ability test system. The results showed that SPD commonly used in lightning surge protection had certain ability to suppress electromagnetic pulse conduction disturbance. Gas discharge tubes presented typical clamping characteristics for wide pulses. MOV and TVS had obvious clamping effect on wide pulses, while had no clamping effect on narrow pulses, but could obviously reduce its peak value. Zener diodes had obvious clamping effect on narrow pulses, and the clamping voltage control accuracy was high.